TRADISI ZIARAH KUBUR SETELAH HARI PERNIKAHAN DALAM PERSPEKTIF HUKUM ISLAM - Sri Wahyuni; Muammar Muhammad Bakry; Musyfikah Ilyas (Universitas Islam Negeri Alauddin Makassar)
Abstract The main problem in this research is How is the Tradition of Pilgrimage to the Grave After the Wedding Day in the Perspective of Islamic Law (Case Study in Bitowa Village, Manggala District, Makassar City). The main problem is divided into two sub-problems, namely 1) What is the public's view of the tradition of visiting the grave after the wedding day in Bitowa Village, Manggala District, Makassar City?, 2) How is the tradition of visiting the grave after the wedding day in the perspective of Islamic law in Bitowa Village, Manggala District, Makassar City. The results of this study indicate that the tradition of visiting the grave after the wedding day is carried out in the Bitowa Village community with the procedures carried out during a grave pilgrimage such as visiting family graves, preparing all preparations before leaving for a grave pilgrimage such as (pots filled with water; flowers; and leaves). pandanus), greet the grave experts, pour water and sow flowers and pandan leaves on the visited graves, face the Qibla when praying at the visited graves, send prayers to the deceased by reciting short suras closed with Surah al-Fatihah. And the wisdom that can be taken is that we always remember that living humans will inevitably experience death, as a mirror to increase the deeds of worship to Allah SWT, and ask Allah for forgiveness for the sins of the deceased through prayer. In Islam the pilgrimage to the grave is a prescribed worship and of course it must be in accordance with what was taught by the Prophet Muhammad, so the grave pilgrimage carried out by the people of Bitowa Village can be done as long as no one violates sharia such as asking for something at the grave. But to pray for it is not a problem. Even if it is a tradition, because it is considered a good tradition. Keywords: Islamic Law, Grave Pilgrimage, Marriage.